A self‐adhesive microneedle patch with drug loading capability through swelling effect. Issue 2 (29th February 2020) - Chew, Sharon W. T.; Shah, Ankur H.; Zheng, Mengjia; Chang, Hao; Wiraja, Christian; Steele, Terry W. J.; Xu, Chenjie
Abstract: Microneedles (MNs) offer a rapid method of transdermal drug delivery through penetration of the stratum corneum. However, commercial translation has been limited by fabrication techniques unique to each drug. Herein, a broadly applicable platform is explored by drug‐loading via swelling effect of a hydrogel MN patch. A range of small molecule hydrophilic, hydrophobic, and biomacromolecule therapeutics demonstrate successful loading and burst release from hydrogel MNs fabricated from methacrylated hyaluronic acid (MeHA). The post‐fabrication drug loading process allows MeHA MN patches with drug loadings of 10 μg cm −2 . Additional post‐fabrication processes are explored with dendrimer bioadhesives that increase work of adhesion, ensuring stable fixation on skin, and allow for additional drug loading strategies.